2019
DOI: 10.1103/physrevlett.123.067202
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Critical Dynamics of a Heisenberg-Ising Chain in a Longitudinal Field: Many-Body Strings versus Fractional Excitations

Abstract: We report a high-resolution terahertz spectroscopic study of quantum spin dynamics in the antiferromagnetic Heisenberg-Ising spin-chain compound BaCo2V2O8 as a function of temperature and longitudinal magnetic field. Confined spinon excitations are observed in an antiferromagnetic phase below TN ≃ 5.5 K. In a field-induced gapless phase above Bc = 3.8 T, we identify many-body string excitations as well as low-energy fractional psinon/antipsinon excitations by comparing to Bethe-Ansatz calculations. In the vici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 56 publications
3
62
0
Order By: Relevance
“…2 as a function of ζ i , the negative zeros of the Airy function Ai(−ζ i ) = 0. The linear dependence on ζ i reflects the spinon confinement in a linear confining potential [8,31], which is set up by the interchain couplings in the magnetically ordered phase [15,18,24,[27][28][29]35]. Above M 7 one can see a broader peak around 0.49 THz (labeled 2M 1 ) and a broad continuum at higher energy (labeled M 1 + M 1 ), consistent with the observation in Ref.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…2 as a function of ζ i , the negative zeros of the Airy function Ai(−ζ i ) = 0. The linear dependence on ζ i reflects the spinon confinement in a linear confining potential [8,31], which is set up by the interchain couplings in the magnetically ordered phase [15,18,24,[27][28][29]35]. Above M 7 one can see a broader peak around 0.49 THz (labeled 2M 1 ) and a broad continuum at higher energy (labeled M 1 + M 1 ), consistent with the observation in Ref.…”
Section: Resultssupporting
confidence: 88%
“…1). The transverse-field Ising-chain quantum critical point is characterized by a peculiar thermodynamic property: With decreasing temperature at the critical field, the Grüneisen parameter converges [29,37,38], in contrast to the divergent behavior for a generic quantum critical point [39].…”
Section: Introductionmentioning
confidence: 99%
“…These studies on spin ladders were partially motivated by Haldane's prediction of a gap in the excitation spectrum for integer-S antiferromagnets [20], as well as by the work of Shiba [21] who suggested that a weak inter-chain coupling between two spin 1/2 Heisenberg chain can explain the occurrence of discrete lines in the Raman spectrum of CsCoCl 3 and CsCoBr 3 [22,23]. Consequently, quasi one-dimensional spin ladders experienced an increasing research activity and the occurrence of confinement in these models has been intensively studied [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], finally leading to remarkable observations through neutron scattering and high-resolution terahertz spectroscopy [41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Due to collective quantum fluctuations, exotic states of matter can emerge near a quantum critical point (QCP) in quantum many-body systems [1][2][3][4][5][6], which have been attracting intensive research [7][8][9][10][11][12][13][14][15][16]. One such paradigmatic system is the transverse field Ising chain (TFIC) in the presence of a longitudinal field.…”
Section: Introductionmentioning
confidence: 99%